Peningkatan Pengetahuan Remaja Tentang Bahaya Akibat Narkotika, Alkohol, Psikotropika Dan Zat Adiktif Lain (NAPZA) Di SMA N 15 Kabupaten Muaro Jambi - Muhammad Dody Izhar; Raden Halim; Fitria Eka Putri (Jurnal Salam Sehat Masyarakat (JSSM), 2019)
Substances classified as drug use refers to a group of substances that have a risk to the user, namely addiction (addiction). Drug is a substance or substance that when it enters the body affects the body, especially the central nervous system / brain so that when abused it will cause physical, psychological or mental disorders, and social functions. Jambi Province is the fourth highest province in Indonesia in narcotics distribution. According to survey data from the central BNN with a prevalence rate of 2.2 or reaching 53,177 inhabitants. This community service aims to increase knowledge about the dangers of drugs so that it becomes the basis of planning for the prevention of drug abuse among students / adolescents. This activity is in partnership with SMA N 15 Muaro Jambi. This activity involves all parties, especially students, as the target of increasing knowledge. Activities are carried out from compiling activity plans to monitoring and evaluating activities according to the specified targets and outputs. There has been an increase in students' knowledge about the dangers of drug use from the results of pre and post tests that have been conducted. The issuance of Decree on the establishment of anti-drug cadres as many as 5 students, as well as publications in the mass media are some of the outcomes that have been produced. Other outcomes are journal articles for public service activities.